Predicting Obsessive Symptoms on the Bases of Metacognitive Beliefs, Responsibility and Latent Aggression - Saman Sadeghpour; Shahram Mohammadkhani; Fatemeh Ayat Mehr (روانشناسی و روانپزشکی شناخت, 2015)
Background: Due to the complex and heterogeneous nature of Obsessive- Compulsive Disorder (OCD), one cannot rely on a theory to explain this disorder. Purpose: So the aim of the current study was to predict OCD based on three variables including latent aggression, metacognitive beliefs and responsibility. Method: A sample of 158 students of kharazmi university (100 female and 58 male) were conveniently selected and answered Maudsley Obsessive Compulsive Inventory (MOCI), Metacognition Questionnaire-30 (MCQ-30), Responsibility and Interpersonal Behaviors and Attitudes Questionnaire (RIBAQ) and Responsibility Attitude Scale (RAS). Data were analyzed using Pearson correlation and stepwise regression analysis. Results: Results indicated that among the predictor variables, uncontrollability metacognitive variable was the best predictor of obsessive symptoms. In the next step worry-responsibility variable had the most predicting potency. Conclusion: So it seems that among this three models of OCD, metacognitive model has the best potency of predicting OCD symptoms and this result can be considered in therapeutic implications.